Connective Expressions as Metadiscourse Markers of Writing Quality in Undergraduate Students’ Expository Writing - BOUDERSA, Nassira (Journal of Human Sciences, 2014)
This article examines third year students’ expository writing and the use of conjunctive expressions (connectives) as markers of good quality essays which is measured in terms of conjunctive expressions’ appropriate use and density, and is reflected by the teachers’ assigned scores to the students’ essays. The expository essays were analyzed for connectives’ use by adopting Halliday and Hasan’s (1976) taxonomy of conjunctive cohesion. The expository essays were divided into two groups, highly scored essays (above 12) and poorly scored essays (below10) to test the correlation between the use of connectives and the quality of essays, reflected by marks. The results show that when students use lot of connective expressions , the quality of their writing will not be good, but when they use a little of connective expressions, the quality of their writing will be good. Accordingly, the hypothesis upon which the research is based, that there is a positive relationship between connective expressions’ use in terms of frequency and appropriacy, and the students’ writing quality, showed negative results and the hypothesis was not, thus, confirmed.